On the calendar of Urusaĝrig - Ozaki, Tohru (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2016)
This article offers a reconstruction of the sequence of month-names at Urusaĝrig (Irisaĝrig, Āl-šarrākī), the site of newly published cuneiform texts. In addition, the leap years and the earlier calendar of Urusaĝrig are discussed.